Pediatric Multisystem Inflammatory Syndrome in a Patient with a Coma with a Hyperosmolar Component in the Manifestation of Type 1 Diabetes Mellitus: Clinical Case - Anastasia N. Lazareva; Yulia V. Tikhonovich; Alexey Yu. Rtishchev; Inna G. Vorontsova; Irina G. Rybkina; Elena E. Petryaykina (Union of pediatricians of Russia, 2024)
Background. Due to the rarity of the combination of emergence diabetes mellitus type 1 (DM1), COVID-19, and multisystem inflammatory syndrome, each reported case represents valuable experience and increases the awareness of medical professionals. Clinical case description. A 7-year-old boy was admitted to the intensive care unit with a diagnosis of diabetes mellitus type 1, first identified. On day 2, ketoacidotic coma with a hyperosmolar component developed, a positive polymerase chain reaction (PCR) test for SARS-CoV-2 was obtained, and a picture of subarachnoid hemorrhage was described according to CT scans of the brain. On day 3, macrohematuria, peripheral edema, pasty complexion were noted; the clinical picture and laboratory examination data corresponded to a "cytokine storm" with the development of multiple organ failure. On day 5, tonic-clonic seizures and bloody discharge from the nasopharynx were noted. On day 6, a negative PCR test for SARS-CoV-2 was obtained, on chest X-rays there was a heterogeneous decrease in pneumatization in the basal sections on both sides, and bilateral hydrothorax. On day 9, meningeal symptoms were noted. On day 14, a repeated episode of a convulsive attack was registered, and changes in the brain according to MRI results were regarded as an inflammatory demyelinating lesion against the background of the course of multisystem inflammatory syndrome and DM or as posterior reversible encephalopathy (PRES syndrome). Against the background of the appointment of immunomodulatory, anticoagulant, antibacterial, antiviral therapy, positive dynamics was noted in the child's condition. On day 18, the patient in a stable condition of moderate severity was transferred to the Department of Pediatric Endocrinology for further treatment. After 14 days, the child was discharged from the hospital in a satisfactory condition. Conclusion. This case report may confirm the risk of developing multisystem inflammatory syndrome in children with DM1 and COVID-19, which requires an interdisciplinary approach and the appointment of therapy included in the standards of management of children with multisystem inflammatory syndrome.